2021
DOI: 10.3390/pharmaceutics13122090
|View full text |Cite
|
Sign up to set email alerts
|

mRNA, a Revolution in Biomedicine

Abstract: The perspective of using messenger RNA (mRNA) as a therapeutic molecule first faced some uncertainties due to concerns about its instability and the feasibility of large-scale production. Today, given technological advances and deeper biomolecular knowledge, these issues have started to be addressed and some strategies are being exploited to overcome the limitations. Thus, the potential of mRNA has become increasingly recognized for the development of new innovative therapeutics, envisioning its application in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 163 publications
(405 reference statements)
0
25
0
Order By: Relevance
“…In vitro transcribed mRNA can be used as a therapeutic agent in preventive vaccines, cancer immunotherapy, or gene replacement therapy (30)(31)(32). However, the utility of IVT RNA exceeds potential clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro transcribed mRNA can be used as a therapeutic agent in preventive vaccines, cancer immunotherapy, or gene replacement therapy (30)(31)(32). However, the utility of IVT RNA exceeds potential clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Discovered in the 1970s, the 5′-cap structure (m7G5′ppp5′N), composed of a 7-methylguanosine nucleoside and a terminal nucleotide linked through a triphosphate bridge in the 5′-mRNA, confers IVT mRNA stability and translation efficiency [ 42 ]. There are three major types of 5′-cap structures, including type O, type I, and type II, which are classified according to whether there is a methylated ribose on the 2′ hydroxyl group of the first or second nucleotide from the 5′ end [ 43 ] ( Figure 4 ).…”
Section: The Principles Of Mrna Vaccine Design and Modificationmentioning
confidence: 99%
“…The 5′-UTR is a noncoding region, but it can help mRNA bind to ribosomes [ 42 ]. Early research suggested that the secondary structure of the 5′-UTR can inhibit mRNA translation, whose symbol is a high GC content [ 49 , 50 ].…”
Section: The Principles Of Mrna Vaccine Design and Modificationmentioning
confidence: 99%
“…As a result of these efforts, co-formulation into lipid nanoparticles (LNPs) has become one of the most successful and commonly used methods for mRNA delivery in vivo (Ickenstein LM, et al, 2019). Because of its reliability, mRNA-LNPs are being extensively utilized in a broad range of new and potential treatments, such as regenerative medicines, vaccines, immunotherapies, and gene editing applications (Baptista B, et al, 2021).…”
Section: Fortunately the Hybridoma Technology Developed By Georges Ko...mentioning
confidence: 99%